#### Answer

$\frac{1}{x-2}$

#### Work Step by Step

$\frac{3}{x^{2}-4}-\frac{1-x}{x^{2}-4}$
=$\frac{3-(1-x)}{x^{2}-4}$
=$\frac{3-1+x}{x^{2}-2^{2}}$
=$\frac{2+x}{(x+2)(x-2)}$
=$\frac{1}{x-2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{1}{x-2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.